Revisiting monetary policy effectiveness in Turkey using a FAVAR model - POLAT, UMURCAN (My University, 2022)
This study aims to perform a comparative analysis of the effectiveness of pass-through of policy rates in Turkey. We explore monetary transmission with different choices of instruments, i.e., the Turkish Lira Reference Interest Rate (TRLIBOR rate), BIST overnight rate, and Divisia money, and under different policy regimes, i.e., inflation targeting and new monetary policy regimes. We estimate a twostage FAVAR model to use all of the available information set and obtain direct responses of disaggregated/sectorial series for the period 2005:12–2018:4. We extend the model setting proposed by Bernanke, Boivin, and Eliasz (2005) by considering the multiple-policy environment in Turkey. Our findings promote arguments that regard policy rate as a poor indicator of the policy stance in Turkey.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); monetary transmission; FAVAR model; policy rate; Divisia index; Turkey